2010
DOI: 10.1007/s10578-010-0208-z
|View full text |Cite
|
Sign up to set email alerts
|

Joint Attention in Parent–Child Dyads Involving Children with Selective Mutism: A Comparison Between Anxious and Typically Developing Children

Abstract: Although joint attention processes are known to play an important role in adaptive social behavior in typical development, we know little about these processes in clinical child populations. We compared early school age children with selective mutism (SM; n = 19) versus mixed anxiety (MA; n = 18) and community controls (CC; n = 26) on joint attention measures coded from direct observations with their parent during an unstructured free play task and two structured tasks. As predicted, the SM dyads established s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
4
19
0
3
Order By: Relevance
“…Furthermore, a study on joint attention, a specific aspect of social communication, reported fewer episodes of joint attention in the SM group than in comparison group. 15 More girls than boys are affected by SM; 3 however, if that is the case in children with comorbid SM and ASD is not clear. A second aim was therefore to examine possible gender differences with regard to presence of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study on joint attention, a specific aspect of social communication, reported fewer episodes of joint attention in the SM group than in comparison group. 15 More girls than boys are affected by SM; 3 however, if that is the case in children with comorbid SM and ASD is not clear. A second aim was therefore to examine possible gender differences with regard to presence of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps these contradictory findings are caused by an observer bias in which the observers seek to attribute mutism to (social) anxiety [43,44]. Even though the overlap between SM and social phobia appears to be high, surprisingly low rates of comorbid social phobia have also been reported [49,50], although part of the children in these studies had been diagnosed with other comorbid anxiety disorders. As a matter of fact, comorbid diagnoses of anxiety disorder other than social phobia are commonly reported in children with SM, including specific phobia [46,50] and separation anxiety disorder [8,51].…”
Section: Introductionmentioning
confidence: 92%
“…Whether SM and SAD represent two distinct conditions is still not settled. Although most descriptive and controlled studies using diagnostic interviews have found high rates of comorbidity between SM and SAD (61–100%; Chavira et al, 2007; Manassis et al, 2007), there have been studies with low rates of SAD in SM (⩽18%; Carbone et al, 2010; Edison et al, 2011; Nowakowski et al, 2011). Children with SAD may also show speech problems, such as longer speech latency, inappropriate tone or low voice volume, and reduced spontaneous speech (Beidel et al, 2019).…”
mentioning
confidence: 99%